Surface alteration driven bi-functional catalytic activity of alkali niobate-N doped graphene composite for exalted oxygen electrochemistry - Suman Kumari Jhajharia; Shashaank Gupta; Zinoy Manappadan; Kaliaperumal Selvaraj; Myoor K. Padmanabhan; Roop L. Mahajan (Applied Surface Science, 2022)
In this work, we establish that surface reconstruction, oxygen vacancies —specifically those located on the catalyst surface, and high crystallinity can be effective in tuning the catalytic activity of perovskite oxides. We report a high-performance electrocatalyst with an orthorhombic perovskite structure (NaNbO3), having an anisotropic surface layer and high crystallinity that exhibits superior activity and durability for the bi-functional oxygen electrochemistry compared to that of a similar perovskite composition with an isotropic surface layer and low crystallinity. The improvement in the electrocatalytic activity for oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) is mainly attributed to the formation of an easy diffusion path on the surface layer due to the ionic movements, enhanced intrinsic activity of the catalytic sites resulting from the higher crystallinity, high oxygen vacancies and a large electrochemically active surface area. The sole key parameter in achieving all the acquired characteristics is the annealing temperature. We believe that the straightforward method of bringing the desired combination of properties by just tweaking the annealing temperature is handy and energy-efficient, and hence easily adoptable.
Keywords: Bi-functionality; N-doped graphene; Oxygen Evolution Reaction; oxygen reduction reaction; perovskite; Surface reconstruction